Simple sequence repeat (SSR) markers for New Zealand mānuka (Leptospermum scoparium) and transferability to kānuka (Kunzea spp.). Issue 3 (3rd July 2017) - Chagné, David; Thrimawithana, Amali; Bowatte, Deepa; Hilario, Elena; Crowhurst, Ross; Smallfield, Bruce; Boase, Murray; Lewis, David; de Lange, Peter; Schwinn, Kathy
ABSTRACT: A multi-allelic genetic marker resource for future genetics studies in mānuka ( Leptospermum scoparium ) and its close relatives has been developed by mining simple sequence repeats (SSR) from a preliminary draft genome assembly of L. scoparium 'Crimson Glory'. In total, 469 and 169 trinucleotide and dinucleotide repeats, respectively, were detected in a set of 89, 619 predicted gene models. Polymerase chain reaction primer pairs were designed for 32 loci exhibiting high sequence similarity to Eucalyptus grandis . These 32 primer pairs were screened over a population of mānuka and 3 accessions of sympatric, related kānuka (genus Kunzea ). The 15 polymorphic SSR markers that were successfully developed are now available for genetic analysis in Myrtaceae.